2017
DOI: 10.1038/onc.2017.28
|View full text |Cite
|
Sign up to set email alerts
|

IL-17C mediates the recruitment of tumor-associated neutrophils and lung tumor growth

Abstract: Chronic obstructive pulmonary disease (COPD) is associated with an increased risk for lung cancer and an aberrant microbiota of the lung. Microbial colonization contributes to chronic neutrophilic inflammation in COPD. Nontypeable Haemophilus influenzae (NTHi) is frequently found in lungs of stable COPD patients and is the major pathogen triggering exacerbations. The epithelial cytokine interleukin-17C (IL-17C) promotes the recruitment of neutrophils into inflamed tissues. The purpose of this study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 45 publications
3
68
0
Order By: Relevance
“…In vitro stimulation of keratinocytes with IL‐17C was sufficient to induce neutrophil migration via CXCL8. This observation is in concordance with a report linking IL‐17C to the recruitment of neutrophils in lung cancer . Of note, IL‐17C induced chemokines of Th1 (CXCL10), Th2 (CCL5) and Th17 immunity (CXCL8), thus pointing out that IL‐17C is not exclusively related to one specific type of T cell‐mediated inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro stimulation of keratinocytes with IL‐17C was sufficient to induce neutrophil migration via CXCL8. This observation is in concordance with a report linking IL‐17C to the recruitment of neutrophils in lung cancer . Of note, IL‐17C induced chemokines of Th1 (CXCL10), Th2 (CCL5) and Th17 immunity (CXCL8), thus pointing out that IL‐17C is not exclusively related to one specific type of T cell‐mediated inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…Further diseases involving the IL-17C/RE axis include psoriasiform skin lesions in inflammatory bowel disease (IBD) patients under anti-TNF-α treatment (53), recurrent aphthous ulcers (20), LPS-induced endotoxin shock (52), and different forms of cancer (38,(54)(55)(56) (Tables 2, 3).…”
Section: Several T H 17-driven Autoimmune Diseases Are Exacerbated Bymentioning
confidence: 99%
“…Moreover, administration of adenoviruses expressing IL-17C and application of recombinant IL-17C result in the recruitment of neutrophils into the lung (15,16). We have shown that IL-17C promotes neutrophilic lung inflammation during acute Pseudomonas aeruginosa pneumonia and inflammationinduced recruitment of neutrophils into the microenvironment of lung tumors (6,17,18).…”
mentioning
confidence: 96%